МЕТОДИ ЗАБЕЗПЕЧЕННЯ СТІЙКОЇ РОБОТИ СЕНСОРНИХ МЕРЕЖ НА БАЗІ БЕЗПІЛОТНИХ ЛІТАЛЬНИХ АПАРАТІВ - Явіся, Валерій Сергійович (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2016)
Methods to ensure sustainable operation of sensor networks based on unmanned aerial vehicles Quality work sensor networks when using unmanned aerial vehicles (UAV) is possible only when the exact positioning of the UAV in space. Discusses the problematic aspects and possible methods to solve this problem, including when deploying their own navigation system based on grouping of nanosatellites.